Thermodynamic analysis for a six stroke engine for heat recovery - Ahmad Azril, Azmi (2012)
The concept adding two more strokes to the Otto cycle to increase fuel efficiency is studied and presented here. It can be thought of as a four-stroke Otto cycle followed by a two-stroke heat recovery steam cycle or also known as six-stroke engine. In this project, thermodynamics analysis was performed for a six stroke internal combustion engine to identify the amount of water needed to be injected for the second power stroke and to identify the cylinder pressure. It was divided into two modes. The first mode, the cylinder was analysed with the exhaust gas. The second mode, the calculation was done without the exhaust gas in the cylinder. Next, another kind of approaches is developed. Based on Jong et al (2009), a computer simulation by using MATLAB was developed based on the Otto cycle which basically 6-stroke is the adding of 2-stroke into 4-stroke engine. Then, performance results can be obtained and compared the results with Jong et al (2009). In the first mode, water is injected depending on the crank angle starting from CA - until CA . From this crank angle, the maximum amount of water needed at CA is 8.8020 × 10-7 cm3 and the minimum amount is 2.7056 × 10-9 cm3 at CA . In the second mode, the calculation was depending on the piston surface and without the exhaust gas in cylinders. This gives the amount of water injected is 29.2188 cm3. From these two modes, the best mode was chosen to calculate the amount of water needed. Next, by using MATLAB, a wide range of engine parameters was studied, such as cylinder pressure and temperatures, density of air, entropy, enthalpy and volume of air in each cycle. For example, for the combustion cycle, the cylinder pressure temperatures, density of air, entropy, enthalpy and volume of air is 2660 K, 7170 kPa, 0.366 ⁄ , 107000 ⁄ , 277.96 ⁄ , and 0.0000588 . From the results, the P-V and T-S diagram were plotted and analysis. Thus, the value of pressure is determined.